Mathematics Teachers’ Perceptions and Practices in the Implementation of Problem-Based Learning for Developing Math Literacy: A Case Study - Garcia, Angielica A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study aimed to understand educators’ perceptions of Problem-Based Learning (PBL) and its application in instructional settings to enhance mathematical literacy at Maximo L. Gatlabayan Memorial National High School during the school year 2023-2024. The research focused on the following objectives: to explore mathematics teachers’ perceptions of PBL for enhancing math literacy, to assess how teachers evaluate the outcomes of PBL initiatives in relation to math literacy development, to identify challenges encountered during PBL implementation, to examine the strategies employed by teachers in implementing PBL, and to propose a model to support PBL implementation. Utilizing a qualitative research design, the study involved semi-structured interviews with twelve purposively selected mathematics teachers from junior and senior high school levels. Data were analyzed through reflexive thematic analysis, following Braun and Clarke’s six-phase framework. Trustworthiness was ensured through credibility, transferability, dependability, confirmability, and reflexivity. Key findings include: (1) teachers view PBL as a tool that significantly improves learners' mathematical literacy by engaging them in real-world problem scenarios; (2) structured assessments, such as rubrics, were utilized to evaluate student learning, demonstrating strong links between PBL and mastery of mathematical concepts; (3) barriers to successful PBL implementation included time constraints and varying student preparedness; (4) varied strategies, including Think-Pair-Share and Real-life Math Modeling, were employed to enhance student participation and critical thinking; and (5) a proposed model for PBL emphasizes collaborative experiential learning,